2002
DOI: 10.1080/088800102753541323
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis With Urokinase in Pediatric Oncology Patients With Central Venous Catheters

Abstract: This study evaluated the effects of urokinase in the prevention of central venous catheter (CVC)-related complications in children with malignancy. Fifteen patients with 16 CVCs (study group A) received an intraluminal application of urokinase (10,000 IU in each catheter lumen for 4 h) once a week. They were monitored prospectively with quantitative blood cultures and ultrasonography (color Doppler ultrasound of the great veins and echocardiography). The rate of complications was compared with that of 15 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
0
33
2
2
Order By: Relevance
“…In two pediatric trials, a statistically lower incidence of occlusive events was demonstrated in the urokinase group, 19-23% versus 31-68% in the control group. 1,56 Furthermore, a prospective trial in adults reported that twice-daily heparin plus weekly urokinase was associated with a lower rate of CVC occlusions compared to heparin alone. 57 Additional studies were unable to corroborate these results (Table 3).…”
Section: Prophylaxismentioning
confidence: 99%
See 2 more Smart Citations
“…In two pediatric trials, a statistically lower incidence of occlusive events was demonstrated in the urokinase group, 19-23% versus 31-68% in the control group. 1,56 Furthermore, a prospective trial in adults reported that twice-daily heparin plus weekly urokinase was associated with a lower rate of CVC occlusions compared to heparin alone. 57 Additional studies were unable to corroborate these results (Table 3).…”
Section: Prophylaxismentioning
confidence: 99%
“…The two pediatric trials also demonstrated a reduced incidence of CVC infection in the treatment group. 1,56 A randomized trial comparing urokinase to placebo found a significantly lower incidence of major CVC-associated coagulase negative staphylococcus infections in the urokinase treatment group with a relative risk of 0.09 (95% CI, 0.01 to 0.5). 59 Two additional studies that were evaluated were unable to support these findings, although in these trials the urokinase was administered as a flush, not allowing the solution to dwell in the catheter lumen for any significant amount of time, which may have affected its efficacy (Table 3).…”
Section: Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective randomized trial compared the efficacy of fortnightly washes with UK 5000 IU/ml versus heparinized solution 100 IU/ml (in volume sufficient to fill the catheter) in preventing the occlusion of partially or totally implanted catheters; patients randomized to receive UK presented a reduction (1.6 times; p=0003) in occlusive events compared to the control group, but unfortunately, the study was discontinued for withdrawal from the market of UK in the USA, and at the time of study discontinuation, the majority of patients had only about 4 months of observation [78]. A prospective non-randomized study investigated the efficacy and safety of thrombolytic agents (UK 10,000 IU per catheter lumen for 4 h once a week) in 15 children with cancer, and the results were compared with those obtained from a series of 15 children treated with thromboprophylaxis; on US Doppler investigation, the rate of asymptomatic thrombosis in the UK-treated group was significantly lower compared with that of the control group and no bleeding complications were reported [79].…”
Section: Primary Pharmacological Prophylaxismentioning
confidence: 97%
“…Heparin-bonded CVLs were also shown to reduce the risk for thrombosis [48,49,50]. The role of adding urokinase to the heparin flushing in the prevention of CVL-related thrombosis is unclear [51,52,53,54]. Thus, available studies do not allow definitive recommendations for CVL prophylaxis in adults or in children and properly designed studies are needed to assess the role of prophylactic anticoagulation, the recommended dosage and frequency of unfractionated heparin instillation in CVL and the use of urokinase and/or heparin-bonded CVLs for preventing CVL-related thrombosis.…”
Section: Prophylaxismentioning
confidence: 99%